1998
DOI: 10.1021/jp9825258
|View full text |Cite
|
Sign up to set email alerts
|

Diffusional Mediation of Surface Electron Transfer on TiO2

Abstract: The results of a kinetic study are reported for cross-surface electron transfer in the reversible oxidation of [Os II (bpy) 2 (4,4′-(CO 2 H) 2 bpy)](PF 6 ) 2 to Os III surface adsorbed to nanocrystalline TiO 2 films on optically transparent ITO (tin-doped indium oxide) electrodes. The kinetics are sensitive to the extent of surface loading. From monolayers adsorbed from CH 3 CN, a percolation threshold of ∼60% was measured. Adsorption isotherms for [Os II (bpy) 2 (4,4′-(CO 2 H) 2 bpy)](PF 6 ) 2 in EtOH and CH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
192
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(207 citation statements)
references
References 10 publications
14
192
0
1
Order By: Relevance
“…S4). A related phenomenon was reported earlier for ½OsðbpyÞð4;4 0 -ðPO 3 H 2 Þ 2 bpyÞ 2þ surfacebound to nanoTiO 2 and attributed to OsðII → IIIÞ oxidation by cross-surface, diffusional electron transfer (28). In this process, site-to-site electron transfer hopping and counter ion transport occur between surface couples providing a cross-surface electron transfer channel to the underlying electrode.…”
supporting
confidence: 73%
“…S4). A related phenomenon was reported earlier for ½OsðbpyÞð4;4 0 -ðPO 3 H 2 Þ 2 bpyÞ 2þ surfacebound to nanoTiO 2 and attributed to OsðII → IIIÞ oxidation by cross-surface, diffusional electron transfer (28). In this process, site-to-site electron transfer hopping and counter ion transport occur between surface couples providing a cross-surface electron transfer channel to the underlying electrode.…”
supporting
confidence: 73%
“…Impedance spectroscopy has proved to be a very useful technique for the characterization of properties of dye solar cells 1,[19][20][21][22] and electrochromic windows. 23 Recently, a new approach has been taken [24][25][26][27][28] toward electric and electrooptic devices formed by molecular functionalized mesoscopic oxides, such as photovoltaic cells, sensors, and Figure 1. Scheme of the two-channel transmission line model for a porous electrode in electrolyte solution.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Ru II and other sensitizers anchored to mesoporous nanocrystalline TiO 2 thin films can be reversibly oxidized in standard electrochemical cells provided that the sensitizer surface coverage exceeds a percolation threshold. [74][75][76] Cyclic voltammetry and spectroelectrochemistry are thus powerful in situ tools for determining formal reduction potentials and absorption spectra of relevant redox states.…”
Section: Charge Separationmentioning
confidence: 99%